Uncovering the Interrelation between Metabolite Profiles and Bioactivity of In Vitro- and Wild-Grown Catmint (Nepeta nuda L.) - Zaharieva, Anna; Rusanov, Krasimir; Rusanova, Mila; Paunov, Momchil; Yordanova, Zhenya; Mantovska, Desislava; Tsacheva, Ivanka; Petrova, Detelina; Mishev, Kiril; Dobrev, Petre I; Lacek, Jozef; Filepová, Roberta; et al. (Metabolites, 2023)
Nepeta nuda L. is a medicinal plant enriched with secondary metabolites serving to attract pollinators and deter herbivores. Phenolics and iridoids of N. nuda have been extensively investigated because of their beneficial impacts on human health. This study explores the chemical profiles of in vitro shoots and wild-grown N. nuda plants (flowers and leaves) through metabolomic analysis utilizing gas chromatography and mass spectrometry (GC-MS). Initially, we examined the differences in the volatiles' composition in in vitro-cultivated shoots comparing them with flowers and leaves from plants growing in natural environment. The characteristic iridoid 4a-α,7-β,7a-α-nepetalactone was highly represented in shoots of in vitro plants and in flowers of plants from nature populations, whereas most of the monoterpenes were abundant in leaves of wild-grown plants. The known in vitro biological activities encompassing antioxidant, antiviral, antibacterial potentials alongside the newly assessed anti-inflammatory effects exhibited consistent associations with the total content of phenolics, reducing sugars, and the identified metabolic profiles in polar (organic acids, amino acids, alcohols, sugars, phenolics) and non-polar (fatty acids, alkanes, sterols) fractions. Phytohormonal levels were also quantified to infer the regulatory pathways governing phytochemical production. The overall dataset highlighted compounds with the potential to contribute to N. nuda bioactivity.
Keywords: bioactivity; phytohormones; volatiles; GC-MS; Nepeta nuda; metabolites